2020
DOI: 10.2196/22079
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Trauma-Focused Therapy for Military Members, Veterans, and Public Safety Personnel With Posttraumatic Stress Injury: Systematic Scoping Review

Abstract: Background A necessary shift from in-person to remote delivery of psychotherapy (eg, teletherapy, eHealth, videoconferencing) has occurred because of the COVID-19 pandemic. A corollary benefit is a potential fit in terms of the need for equitable and timely access to mental health services in remote and rural locations. Owing to COVID-19, there may be an increase in the demand for timely, virtual delivery of services among trauma-affected populations, including public safety personnel (PSP; eg, par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 70 publications
5
48
0
Order By: Relevance
“…In particular, issues relating to privacy are especially salient given not only the widespread stigma associated with mental health concerns in the military or PSP organizations but also the sensitivity of disclosures that may occur when working with MMs or PSP who have high security clearance. Despite these barriers, encouraging evidence supporting the use of digital health was identified through a systematic scoping review conducted by members of this research team in advance of this study regarding digital health delivery of trauma therapies for MMs, veterans, and PSP [19]. This review illustrated that the delivery of cognitive processing therapy (CPT), prolonged exposure therapy, and behavioral activation therapy using videoconferencing demonstrated comparable effectiveness to in-person treatment in reducing posttraumatic stress disorder symptoms in MMs and veterans [19].…”
Section: Digital Health For Mms Veterans and Pspmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, issues relating to privacy are especially salient given not only the widespread stigma associated with mental health concerns in the military or PSP organizations but also the sensitivity of disclosures that may occur when working with MMs or PSP who have high security clearance. Despite these barriers, encouraging evidence supporting the use of digital health was identified through a systematic scoping review conducted by members of this research team in advance of this study regarding digital health delivery of trauma therapies for MMs, veterans, and PSP [19]. This review illustrated that the delivery of cognitive processing therapy (CPT), prolonged exposure therapy, and behavioral activation therapy using videoconferencing demonstrated comparable effectiveness to in-person treatment in reducing posttraumatic stress disorder symptoms in MMs and veterans [19].…”
Section: Digital Health For Mms Veterans and Pspmentioning
confidence: 99%
“…Despite these barriers, encouraging evidence supporting the use of digital health was identified through a systematic scoping review conducted by members of this research team in advance of this study regarding digital health delivery of trauma therapies for MMs, veterans, and PSP [19]. This review illustrated that the delivery of cognitive processing therapy (CPT), prolonged exposure therapy, and behavioral activation therapy using videoconferencing demonstrated comparable effectiveness to in-person treatment in reducing posttraumatic stress disorder symptoms in MMs and veterans [19]. This scoping review identified significant knowledge gaps.…”
Section: Digital Health For Mms Veterans and Pspmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been amplified by the recent COVID-19 pandemic when virtual health solutions have become increasingly common in all health care practices, including those in military environments. Although most studies addressing technology attitudes, beliefs, acceptance, and usability within military and veteran populations are US based, current evidence suggests that the military population is willing to use digital health and mHealth technologies [25][26][27]. Regardless of the context for technological innovation, adequate technology acceptance and usability is key to its uptake within that environment and culture.…”
Section: Technology Acceptance and Usability In Health Care And Military Contextsmentioning
confidence: 99%
“…For example, it may not be possible to provide personal hygiene and maintain physical distance in convicts and detainees who cannot see their relatives due to visiting ban. All these stressful life events require caution in these special groups who are at risk in terms of suicidal behavior during and after the pandemic [59]. In addition, it should be kept in mind that people who work in funeral burials, for whom no risk for suicidal behavior has been identified, may be in a risk group for suicidal behavior.…”
Section: Risk Groups In Suicidal Behavior Associated With Covid-19mentioning
confidence: 99%